1977
DOI: 10.1149/1.2133103
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Metal Overlayers on Gallium Phosphide Photoelectrodes

Abstract: A recent publication by Nakato et al., suggested that thin gold overlayers could be made to protect normalGaP photoelectrodes from corrosion. Repetition of their experiments, including simultaneous measurement of the gold potential, duplicates the volt‐ampere characteristics reported in that paper. Gas evolution was not observed, and the gold potential remains too low to decompose water at its surface. An alternative interpretation of the action of the Au overlayer is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

1980
1980
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 3 publications
1
20
0
1
Order By: Relevance
“…70 Later, Wilson et al revisited such a metal-layer stabilization strategy by studying an Au/nGaP combination. 71 The energy-band diagram indicated that the metal overlayer formed a buried Schottky junction with n-GaP; hence this metal coating contacted the electrolyte (similar to Figure 5b). …”
Section: Metals and Metal Silicide Protective Layersmentioning
confidence: 69%
See 1 more Smart Citation
“…70 Later, Wilson et al revisited such a metal-layer stabilization strategy by studying an Au/nGaP combination. 71 The energy-band diagram indicated that the metal overlayer formed a buried Schottky junction with n-GaP; hence this metal coating contacted the electrolyte (similar to Figure 5b). …”
Section: Metals and Metal Silicide Protective Layersmentioning
confidence: 69%
“…Attempts to protect n-type GaP (n-GaP) and n-type Si (n-Si) photoanodes in the late 1970s relied on thin layers of Au, Pd, and Ag films deposited by electron-beam evaporation or sputtering . Later, Wilson et al revisited such a metal-layer stabilization strategy by studying a Au/n-GaP combination . The energy-band diagram indicated that the metal overlayer formed a buried Schottky junction with n-GaP; hence this metal coating contacted the electrolyte (similar to Figure b).…”
Section: Protection Of Photoanodesmentioning
confidence: 99%
“…Several noble metals including Pd, 133 Pt, 134 and Rh, 135 have been studied on Si during the early development of Si photoelectrochemistry, as well as other materials. 136 Regarding the thermodynamic and kinetic problems of Si, the metal coating was initially proposed to suppress photocorrosion of n-Si and catalyze a HER on p-Si. A thin continuous layer of metal and the Schottky junction formed are desired to isolate Si from a direct contact to the oxidizing electrolyte, to allow a minimal optical loss, to provide an effective barrier for the majority carriers, and to provide sufficient driving force for the photoinduced minority carriers.…”
Section: Metals Metal Alloys Silicides and 1d/2d Carbonmentioning
confidence: 99%
“…There is ample evidence in the literature to show that protic solutions can dope n-Ti02 electrodes. [55][56][57][58][59] The data on p-InP contacts demonstrate that no electrically active gas is penetrating significantly into the space charge region of this material. The Mott-Schottky plots have identical slopes and therefore the samples have identical carrier concentrations.…”
Section: Aspnes and Hellermentioning
confidence: 99%